The Growth of Lactobacillus fermentum Isolated from Quail Intestine on Rice Bran Medium - Umi Kalsum; O. Sjofjan (Journal of Tropical Life Science, 2012)
The objective of this study was to investigate the growth of Lactobacillus fermentum isolated from the intestine of Japanese quail (Coturnix japonica) on medium variation of rice bran meal. The influence of this medium preparation on the cell number and produce of lactic acid of L.fermentum was evaluated every six hour in 36-hour incubation. A randomized block design was used to assign three variation of rice bran medium (6, 9 and 12) %. The result showed that the higest cell number was in 9 % rice bran medium at pH 4.7 at 12th hour was 5.2 x 1010 CFU/ml and the highest lactic acid concentrations were 0.57 %. The fastest speed of growth in 9 % rice bran medium was 0.92 generation/hour and generation time 45 minutes. In conclusion, the optimum growth of L.fermentum was in 9 % rice bran medium at 12th hour.Keywords: Lactobacillus fermentum, growth, quail, rice bran.